Extraction of oil from rubber (Hevea brasilensis) seed by using soxhlet extraction: article - Mohd Zahid, Muhammad Al’Aqib; Veny, Harumi (2018)
The extraction of oil from rubber (Hevea brasillensis) seed by using solvent extraction Soxhlet extraction techniques. Soxhlet technique is extraction method to produce high percentage of oil yield and practically easy to use. The size is 355, 500 and 700μm. It is found that rubber seed with 355μm produce percentage of oil yield 42.13% percentage of oil yield for 500 and 700μm rubber seed were 37.83% and 18.96% respectively. These studies n-hexane and methanol solvent. The results show that, the percentage of oil yield for the methanol is lower than n-hexane solvent the effect of mass to solvent ratio compared between 1:4, 1:5, 1:10 and 500μm rubber seed and n-hexane as the solvent 1:4 with 31.39%.